2018
DOI: 10.3390/buildings8120171
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Approach for the Annual and Spatial Evaluation of the Comfort Classes of Daylight Glare Using Vertical Illuminances

Abstract: A simplified approach to calculate the daylight glare comfort class (imperceptible, perceptible, disturbing, or intolerable glare) on annual basis and for a grid of points in a space is presented. This method relies on the calculation of the vertical illuminance (Ev) for each grid point only, which is compared to an Ev threshold value for each daylight glare comfort class. These Ev threshold values are determined through a comparison with the Daylight Glare Probability (DGP) values on an annual basis through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Harrold and others proposed the concepts and formulas of Visual Comfort Probability (VCP) [26]; Wienold & Christoffersen [27] developed Daylight Glare Probability (DGP) calculated by glare in vertical illumination. Hirning [28] validated previous glare measurements and introduced the Unified Glare Probability (UGP) as a predictor of glare discomfort, by using a combination of natural lighting mapping and user questionnaires [29]. Several studies on visual comfort involving user questionnaires have been conducted, such as by Chinazzo, which concluded that no significant differences in evaluation of visual perception were found between the moderate and high levels of daylight, especially in terms of visual comfort [30].…”
Section: Literature Reviewmentioning
confidence: 97%
“…Harrold and others proposed the concepts and formulas of Visual Comfort Probability (VCP) [26]; Wienold & Christoffersen [27] developed Daylight Glare Probability (DGP) calculated by glare in vertical illumination. Hirning [28] validated previous glare measurements and introduced the Unified Glare Probability (UGP) as a predictor of glare discomfort, by using a combination of natural lighting mapping and user questionnaires [29]. Several studies on visual comfort involving user questionnaires have been conducted, such as by Chinazzo, which concluded that no significant differences in evaluation of visual perception were found between the moderate and high levels of daylight, especially in terms of visual comfort [30].…”
Section: Literature Reviewmentioning
confidence: 97%
“…For the DGPs model, its application enabled performance in the target spaces concerning the large-area sources of glare with no direct sun hitting the eyes, as per Wienolds' consideration [16,20]. Window size greatly influences occupants [50], with the daylight glare simulation study of Giovannini et al [33] finding that the rate of VLT affected glare perception with the amount of vertical illuminance. However, shading device usage resulted in low conditions of light inside occupied spaces; daylight glare was never experienced by the users.…”
Section: Surveyed Datamentioning
confidence: 99%
“…Since the vertical illuminance dominated subjective responses with its contributions to DGPs, the illuminance-based approach was generally applied to evaluate daylight glare concerning the DGPs model. The simulation study of Giovannini et al [33] found that this simplified approach to calculate the daylight glare comfort classes using vertical illuminance had a good correlation with DGP evaluation, and it was less time consuming in practical terms. Thus, it is worthwhile to adopt this model for daylight glare evaluation in post-occupancy survey of buildings, and its usability needs to be explored under the contextual study.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the method was determined through the comparison with DGP values by applying a fault-detection technique. A preliminary paper that describes the study was published by the same Authors (Giovannini et al, 2018). In this paper the results of an expanded study are presented: in this the new simplified approach is tested for a larger number of viewpoints and, for each viewpoint, considering a plurality of view directions.…”
Section: 16mentioning
confidence: 99%